Problematics of Determining the Lineage of Children Born Before Marriage - Rifal Muhammad; Marzuki, Marzuki; Ida Lestiawati; Dicki Patadjenu (State Islamic University Datokarama Palu, 2024)
This study discusses the problems of determining the nativity of children born out of wedlock. The method used in this study is qualitative phenomenological research. Phenomenological qualitative research is a research procedure that produces descriptive data based on people's spoken words, observable behavior, and actual problems in society. The authors collected data through direct observation, in-depth interviews, and written material analysis. Data analysis follows three stages: data reduction, presentation, and verification. In this study, the research subject is the phenomenon of children born out of wedlock and the determination of their lineage. The results of this study show that the father cannot completely rely on the determination of the fate of a child born out of wedlock. This refers to the Jumhur or agreement of the majority of ulama. Determining the birth of a child who is pregnant out of wedlock rests entirely with the mother, however, the marriage of a woman who is pregnant before married can still be appropriately registered. Remembering that every child has the same rights. After conducting research and analysis, the authors have suggestions that can be input to the Bunta District Religious Affairs Office, Banggai Regency, namely as follows: The Bunta District Religious Affairs Office, Banggai Regency, is expected to be able to carry out more effective outreach and strive to provide education on certain activities to avoid cases of pregnancy out of wedlock. The sub-district and village governments approach religious values so that things that trigger promiscuity can be avoided as early as possible. The implications of this research are that it is hoped that it can make a contribution to society in general and students in particular, such as teenagers so that they can refrain from immoral actions that can harm society and religious norms.